Perancangan dan Implementasi Aplikasi YouTube Downloader Pro Berbasis Python - Fauzan Abdi Alam Alsalam; Della Putri Kinanti; Chairul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This research aims to design and implement a Python-based YouTube Downloader Pro application that can be used to effectively download videos from the YouTube platform. This application was developed to help users access video content offline. The research methods include requirements analysis, system design, implementation, and testing using black-box and white-box methods. The test results indicate that the application runs according to the expected functionality.